UPENDING TRADITIONAL WRITING INSTRUCTION: A PLEA TO TEACH VISUAL TEXTS IN L1 AND L2 CLASSROOMS - M. Todd Harper (Universitas Katolik Indonesia Atma Jaya, 2007)
With the advent of multi-media, interpreting visual texts has become an important function of literacy. Yet, few L1 or L2 English writing classes devote any time to these texts, in part because many L1 and L2 teachers do not know how to interpret these texts themselves. This article suggests two methods for understanding visual discourse: the interpretation of images, pictures, and graphics within a system of similar visual artifacts and the location of those images, pictures, and graphics within a historical and cultural context. As an example, two graphics on the University of Athens’ homepage were examined. Keywords: visual texts, visual discourse, images, literacy, pictures, graphics